Electrical Conductivity Sensor for Plant Substrates - Yawar Abbas; Milou Jaspers; Rached Moalla; Joris van Nieuwstadt; Marcel A. G. Zevenbergen (Proceedings)
Measuring the electrical conductivity (EC) of plant substrates is an effective way to assess their nutrient content. This study aims to compare the performance of EC sensors with varying electrode sizes and spacings when embedded in a plant substrate. The range of electrode sizes and spacings varied from 0.1 mm to 10 mm. The EC electrodes were embedded in a porous plant substrate and subjected to wet–dry cycles. The results showed that the electrodes with larger electrode dimensions and spacing produce valid EC values.